2021
DOI: 10.1002/jnr.24955
|View full text |Cite
|
Sign up to set email alerts
|

Comparing axon regeneration in male and female mice after peripheral nerve injury

Abstract: Axons in the adult mammalian central nervous system fail to regenerate after injury. By contrast, spontaneous axon regeneration occurs in the peripheral nervous system (PNS) due to a supportive PNS environment and an increase in the intrinsic growth potential induced by injury via cooperative activation of multifaceted biological pathways. This study compared axon regeneration and injury responses in C57BL/6 male and female mice after sciatic nerve crush (SNC) injury. The extent of axon regeneration in vivo wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…In our series, four of five patients were male, which reflects the gender disbalance of brachial plexus injuries, which mainly affect men [15]. Even though the literature suggests a pro-regenerative effect of androgen hormones in nerve regeneration, there is no clear evidence for superior results in males [24][25][26]. For evaluation of a clinical gender difference in peripheral nerve regeneration a bigger cohort with a representative number of female patient would be necessary.…”
Section: Discussionmentioning
confidence: 83%
“…In our series, four of five patients were male, which reflects the gender disbalance of brachial plexus injuries, which mainly affect men [15]. Even though the literature suggests a pro-regenerative effect of androgen hormones in nerve regeneration, there is no clear evidence for superior results in males [24][25][26]. For evaluation of a clinical gender difference in peripheral nerve regeneration a bigger cohort with a representative number of female patient would be necessary.…”
Section: Discussionmentioning
confidence: 83%
“…TG1, TG3, and their substrates are localized in the epidermis or oral mucosal epithelium and contribute to the formation of CE during the differentiation of the epidermis or oral mucosal epithelium 8 . Although some investigators reported mRNA expressions of TG1, SPRR1a, and SPRR3 in large vessels such as the aorta and vena cava, injured peripheral nerve, and atherosclerotic vessels, respectively, the mRNA expressions were described in limited cells and pathological conditions 28–30 . Thus, our method can scarcely interfere with our mRNA expression results.…”
Section: Discussionmentioning
confidence: 89%
“…8 Although some investigators reported mRNA expressions of TG1, SPRR1a, and SPRR3 in large vessels such as the aorta and vena cava, injured peripheral nerve, and atherosclerotic vessels, respectively, the mRNA expressions were described in limited cells and pathological conditions. [28][29][30] Thus, our method can scarcely interfere with our mRNA expression results.…”
Section: Discussionmentioning
confidence: 99%
“…Although most nerve injuries in humans affect males, few studies have concentrated on investigating nerve regeneration mechanisms in male and female rats or mice in clinically relevant injury and repair and reconstruction models [30,[145][146][147][148]. Gender-specific perspectives are relevant in view of reported enhancement of axonal outgrowth in males, and sustained synaptic inputs by exercise are observed in male and female rats, but the requirements of exercise protocols differ between sexes [30,[145][146][147][148].…”
Section: Nerve Regeneration In Males and Females And In Diabetesmentioning
confidence: 99%
“…Although most nerve injuries in humans affect males, few studies have concentrated on investigating nerve regeneration mechanisms in male and female rats or mice in clinically relevant injury and repair and reconstruction models [30,[145][146][147][148]. Gender-specific perspectives are relevant in view of reported enhancement of axonal outgrowth in males, and sustained synaptic inputs by exercise are observed in male and female rats, but the requirements of exercise protocols differ between sexes [30,[145][146][147][148]. In contrast to studies examining gender effects on nerve regeneration after a nerve crush, axonal outgrowth seems to be better in healthy and diabetic male rats than in corresponding healthy and diabetic female rats after a sciatic nerve injury and direct repair [30].…”
Section: Nerve Regeneration In Males and Females And In Diabetesmentioning
confidence: 99%